Business Process Reengineering In Library Book Lending System - Tsani, Mutiara; Nur Aulia, Adiva; Nuryasin, Ilyas (PT Mattawang Mediatama Solution, 2023)
The development of information technology is in line with the development of internet use in Indonesia, so that organizations that are unable to adapt to information technology and the internet will find it difficult to develop in the face of today's global competition. Computerized data processing contributes greatly when compared to manual data processing. SMA Muhammadiyah 2 has a library which is still relatively new and not many books. This is very inefficient, because in addition to wasting paper, data is inaccurate, filing becomes unorganized and messy. One way to increase effectiveness and efficiency is to use Business Process Reengineering (BPR) methods to improve old business processes. These stages consist of data collection, business process analysis, business process throughput efficiency test, process redesign refinement, process redesign recommendation, throughput efficiency test business process recommendation, comparison of throughput efficiency test results, solutions. The results obtained from this study are 2 the main processes studied are the process of borrowing books and the process of returning books, which are old processes that have efficiency values of 46% and 35%. However, after re-engineering the business processes of the two processes it was able to reach 100%, which found 5 processes that were eliminated and 5 processes that were automated online.